Uji Median Pengaruh Utama dan Interaksi dalam Percobaan Berfaktor - Nugroho, Sigit (GRADIEN : Jurnal Ilmiah MIPA, 2007)
Factorial experiments with fixed effects in randomized complete block design can be modeled as Yijk = ? + ?i +? j +?k + (?? ) jk +? ijk i =1, 2,...,b j = 1, 2,...,t k = 1, 2,...,m . To test main effects and its interaction when basic assumptions are met is using the F test (ANOVA). Nonparametric alternative testing for maineffects median and interaction median is discussed in this paper.Â Â Â